Autolysis of rainbow trout (Oncorhynchus mykiss) by-products: Enzymatic activities, lipid and protein oxidation, and antioxidant activity of protein hydrolysates. (April 2021) - Nikoo, Mehdi; Regenstein, Joe M.; Noori, Farzaneh; Piri Gheshlaghi, Shima
Abstract: Autolysis (at fixed temperatures (40, 50, 60 °C) or gradually increasing temperatures (40-60 °C) with different times) was used to produce protein hydrolysates from rainbow trout processing by-products. Total proteolytic and trypsin activities with fixed temperatures was higher than gradually increasing temperatures, decreased with increasing autolysis time and temperature with fixed temperatures (P ≤ 0.05). TCA-soluble peptides decreased with increasing autolysis times from 1 to 3 h (P ≤ 0.05). Autolysis increased peroxide value and thiobarbituric acid-reactive substances in both lipids and hydrolysates, particularly with gradually increasing temperatures (P ≤ 0.05) and was associated with oxidation of polyunsaturated fatty acids. Sulfhydryl groups decreased, while protein carbonyls and solubility were increased with fixed temperatures at higher temperatures (50 and 60 °C) or with gradually increasing temperatures at longer autolysis time (P ≤ 0.05). Free radical scavenging activity and the metal chelating ability of hydrolysates were governed by autolysis times and temperatures. Results of size exclusion chromatography-high performance liquid chromatography indicated that autolysis for 1 h at lower temperature (40 °C) was sufficient to produce autolysates rich in small peptides from rainbow trout by-products. Autolytic hydrolysis might be useful for production of such protein hydrolysates. Highlights: Gradual or fixed autolysis at higher temperature lowered the enzyme activity. All protein hydrolysates were rich in small peptides (93–97% < 1 kDa). Autolysis for 1 h at 40 °C was long enough to produce hydrolysates. Autolytic hydrolysis might be useful for production of protein hydrolysates.